Modern Applications of Clinical Pharmacy in Enhancing Patient Care - Saleem, Bara Nahdh; Abbas, Shahad Alaa; Majeed, Saif Hatem; Jawaad, Huthaifa Ezzulddin Mohammed; Mustafa, Mohammed A. (Journal of Science in Medicine and Life, 2025)
The modern applications of clinical pharmacy significantly contribute to improving patient care through evolving pharmacist roles from traditional medication dispensing towards integrated clinical practices. Clinical pharmacists are increasingly embedded in healthcare teams, enhancing medication management, therapeutic outcomes, and patient safety. Key findings highlight the growing provider satisfaction with clinical pharmacist integration into primary care and hospital settings, underscoring pharmacists' proactive roles in patient management, medication optimization, and improving patient safety and quality of life. Despite these advancements, challenges persist, including the need for standardized clinical evidence, robust research methodologies, and broader scalability of interventions. Policymakers and healthcare systems are encouraged to support further academic collaboration and systematic evaluations to fully leverage clinical pharmacy's potential in enhancing patient care globally, particularly in contexts of multimorbidity, polypharmacy, and patient-centered care.